Multicellular oxidant defense in unicellular organisms. - Ma, M (1992)
Although catalase is thought to be a major defense against hydrogen peroxide (H2O2), the catalase activity within individual Escherichia coli fails to protect against exogenous H2O2. Contrary to earlier reports, we find that dilute suspensions of wild-type and catalase-deficient E. coli are identical in their sensitivity to H2O2, perhaps because even wild-type, catalase-positive E. coli cannot maintain an internal/external concentration gradient of this highly diffusible oxidant. However, concentrated suspensions or colonies of catalase-positive E. coli do preferentially survive H2O2 challenge and can even cross-protect adjacent catalase-deficient organisms. Furthermore, high-density catalase-positive--but not catalase-negative--E. coli can survive and multiply in the presence of competitive, peroxide-generating streptococci. These observations support the concept that bacterial catalase may defend colonial, but not individual, E. coli against environmental H2O2. Group protection by the activity of enzymes that mitigate oxidative stress may have been a driving force in the evolution of multicellular organisms.